Drivers of the use of AI-powered tools in academic research: A study of university students in South Africa - Ngomane, Danisile Priscilla (University of the Witwatersrand, Johannesburg, 2024)
The integration of Artificial Intelligence (AI) across various sectors, including education, has garnered significant attention due to its potential to enhance productivity, accuracy, and innovation. There has been a notable lack of research focusing on students' adoption of AI tools in research settings, within the context of South Africa. The primary objective of this study was to provide insights to inform strategies aimed at facilitating the effective implementation of AI-powered technologies within the academic research landscape. The study employed a theoretical framework grounded in the Technology Acceptance Model (TAM), which provides a foundation for understanding individuals' acceptance or rejection of technology. The study aimed to investigate the drivers influencing university students' utilisation of AI tools in educational research settings. Adopting a positivist research philosophy, the study utilised a quantitative research design as the primary inquiry strategy. This involved the administration of a research survey to collect and analyse numerical data, enabling the testing of hypotheses, identification of patterns, and quantification of relationships between variables. The study employed a cross-sectional time horizon and utilised convenience sampling to administer a survey questionnaire to 271 final-year undergraduate and postgraduate students at Witwatersrand University. Analysis of the collected data using descriptive and inferential statistics revealed several key findings. A positive attitude towards utilising AI tools was found to be driven by perceived usefulness, perceived ease of use, prior knowledge, and awareness about the tools. This relationship was moderated by factors such as trust and self-efficacy. The AI tools were primarily utilised for tasks such as searching and summarising articles, writing, editing grammar, and making unbiased judgments about articles. Importantly, students were influenced by the perceived benefits derived from using specific AI tools, and the ease of use associated with these tools. This research study findings suggest that promoting awareness of AI tools among university students has the potential to enhance research outcomes, improve scholarly efficiency and increase overall effectiveness. As the demand for AI technologies continues to grow, integrating them into higher education settings holds promise for unlocking substantial benefits and transforming the academic research landscape.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Artificial intelligence; Technology Acceptance Model; Perceived usefulness; Perceived ease of use; Perceived information effectiveness; Social influence; Prior knowledge and awareness; Trust; Self-efficacy; UCTD; SDG-8: Decent work and economic growth